CONNECTION OF PRECAST BEAM WITH HIGH PERFORMANCE STRENGTH OF CONCRETE (HPSC) SYSTEM - Hermawan, Andrias Rudi; Setiawan, Yanuar; Suripto; Sasmita, Eka Mulya (POLITEKNIK NEGERI JAKARTA, 2025)
The application of high-performance strength concrete (HPSC) in precast beam systems is gaining attention as a means to enhance construction efficiency and structural performance. Previous studies, such as those by Graybeal, have demonstrated the effectiveness of ultra-high-performance concrete (UHPC) in precast bridge deck applications. Similarly, materials like epoxy grout, epoxy-based grout, and rapid-set concrete have shown favorable properties for accelerating construction processes and improving durability. This research aims to evaluate the feasibility of using HPSC in precast beam connections, specifically to reduce the required length of reinforcement at the joint. The goal is to develop a system that can be effectively implemented in global construction practices. The study investigates a precast beam system using HPSC and compares it to a conventional cast-in-place beam. The focus is on key performance metrics including deflection, ultimate load capacity, and ductility. The influence of compressive strength on reinforcement length reduction is assessed in reference to ACI guidelines, which suggest that higher concrete compressive strength allows for shorter rebar development lengths. The precast beam (P1) utilizing the HPSC system achieved a compressive strength of fc’ = 44.81 MPa at the connection. Compared to the conventional beam (K1), P1 showed improved structural behavior, with a reduced deflection of 40.11 mm at an ultimate load of 110.02 kN, whereas K1 exhibited a deflection of 138.11 mm at an ultimate load of 113.82 kN. The ductility of the HPSC system was measured at 4.81, indicating enhanced deformation capacity under load. The findings confirm that the use of HPSC in precast beam connections not only meets structural requirements but also contributes to a reduction in reinforcement length. This supports faster and potentially more costeffective construction, aligning with global needs for innovative and efficient building practices.